Evaluation of firefly algorithm and cuckoo search algorithm for PV MPPT application (2017)
The simulation and discussion of two metaheuristic maximum power point tracking techniques (MPPT) for a photo-voltaic (PV) system under different irradiance conditions is shown, namely Firefly Algorithm and Cuckoo Search Algorithm. The PV system, the global MPPT problem and techniques are addressed. Evaluation of performance is done based on the integral absolute error and efficiency mainly. Cuckoo Search yields better overall results under uniform irradiance conditions, under partial shading conditions and under different ambiance temperatures than the Firefly Algorithm. The importance of well distributed initial set of solutions for these algorithms is addressed and validated.